Fostering Community Engagement: Creating Child-Friendly Villages - Rani Sri Agustina; Muhamad Uut Lutfhi (Faculty of Law, Universitas Sultan Ageng Tirtayasa, 2023)
Community Service for fostering community engagement in Bandung Village, Banjar Sub-district, Pandeglang Regency, to Actualize a Child-Friendly Village. This initiative aims to support government programs dedicated to enhancing child welfare, fostering the growth of healthy, intelligent, joyful, and morally upright Indonesian children, and shielding them from various forms of violence, exploitation, and discrimination. The service employs a counseling method to engage with the community. It is anticipated that, following the completion of this service initiative, the residents of Bandung Village will possess a deeper understanding of child welfare and protection. This understanding will, in turn, ensure that all children in Bandung Village have the opportunity to thrive, experiencing safety and comfort in their community.